Experimental investigation on vapor-liquid equilibrium for 1, 1-difluoroethane(R152a) +trans-1, 3, 3, 3-tetrafluoropropene (R1234ze(E)) binary systems. (December 2022) - Liao, Yu; Dai, Yuande; Xu, Chaoping
Highlights: Vapor-liquid equilibrium of the binary mixture R152a/R1234ze(E) was investigated experimentally at four temperatures between 298.15 K and 328.15 K for the first time. The PR + vdW model was presented to calculate the thermodynamic properties of R152a + R1234ze(E) from 298.15 to 328.15 K. Abstract: At present, environmental impact is considered as primary index in refrigerant selection. R1234ze(E) is an environmentally friendly alternative to R22, but it has drawbacks of poor cycling performance and low refrigerating capacity. R152a has certain flammability though having excellent thermodynamic properties. Therefore, based on their complementary advantages, R1234ze(E) is blended with R152a to be a new mixture. Vapor-liquid equilibrium (VLE) data is the basis of calculating the thermodynamic properties of mixtures. This paper presented the experimental data on the vapor-liquid equilibrium of the binary mixture R152a/R1234ze(E) measured up to 328.15 K for the first time, which was measured by the liquid-phase cycling method. The Peng-Robinson (PR) equation of state (EOS) in conjunction with van der Waals (vdW) mixing rule was used to construct a computational model to correlate the experimental data. The model exhibited a high degree of agreement with the experimental result for binary mixture R152a/R1234ze(E). The maximum average absolute relative deviation of pressure (AARD p ) and the average absolute deviation of vapor-phase mole fraction (AAD y ) for the model were 0.34% and 0.003, respectively.